2022
DOI: 10.3390/ma15030849
|View full text |Cite
|
Sign up to set email alerts
|

Phase Analysis and Thermoelectric Properties of Cu-Rich Tetrahedrite Prepared by Solvothermal Synthesis

Abstract: Because of the large Seebeck coefficient, low thermal conductivity, and earth-abundant nature of components, tetrahedrites are promising thermoelectric materials. DFT calculations reveal that the additional copper atoms in Cu-rich Cu14Sb4S13 tetrahedrite can effectively engineer the chemical potential towards high thermoelectric performance. Here, the Cu-rich tetrahedrite phase was prepared using a novel approach, which is based on the solvothermal method and piperazine serving both as solvent and reagent. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…For instance, Ge and Sn doping were recently explored, exhibiting a compositional limit of about x = 0.6 in Cu 12-x (Ge, Sn) x Sb 4 S 13 (Kosaka et al, 2017). On another note, Ag (Pattrick and Hall, 1983) and Au (Zazakowny et al, 2022) substitution has been shown to be possible in synthetic tetrahedrites, and Pb doping (Cu 11 PbSb 4 S 13 ) demonstrated zT enhancements of about 40% at 723 K when compared to Cubased compositions (Huang et al, 2018). Regardless of the costeffectiveness and toxicity of these tetrahedrites, these studies are evidence that multitudinous elemental substitutions have yet to be explored.…”
Section: Doped and Substituted Tetrahedritesmentioning
confidence: 99%
“…For instance, Ge and Sn doping were recently explored, exhibiting a compositional limit of about x = 0.6 in Cu 12-x (Ge, Sn) x Sb 4 S 13 (Kosaka et al, 2017). On another note, Ag (Pattrick and Hall, 1983) and Au (Zazakowny et al, 2022) substitution has been shown to be possible in synthetic tetrahedrites, and Pb doping (Cu 11 PbSb 4 S 13 ) demonstrated zT enhancements of about 40% at 723 K when compared to Cubased compositions (Huang et al, 2018). Regardless of the costeffectiveness and toxicity of these tetrahedrites, these studies are evidence that multitudinous elemental substitutions have yet to be explored.…”
Section: Doped and Substituted Tetrahedritesmentioning
confidence: 99%
“…However, materials with low thermal conductivity usually contain heavy and hazardous elements [5][6][7][8], which is in contradiction with the required low weight of thermoelectric devices [9,10] and even more crucial for the thermal barrier coatings used for the protection of aircraft turbines [4]. However, a lot of recent works show that ultralow thermal conductivity can be achieved even in materials consisting of lightweight elements through the crystal structure complexity engineering and chemical bonding hierarchy [3,[11][12][13][14][15]. Among the most successful approaches for the reduction of lattice thermal conductivity are the phonon-liquid electron-crystal (PLEC) concept (which is based on the liquid-like behavior of superionic conductors) [2,12,13,16], bonding anisotropy in layered structures [8,17,18], lattice anharmonicity induced by the lone-pairelectrons [5,[19][20][21] and bonding inhomogeneity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, a lot of recent works show that ultralow thermal conductivity can be achieved even in materials consisting of lightweight elements through the crystal structure complexity engineering and chemical bonding hierarchy [3,[11][12][13][14][15]. Among the most successful approaches for the reduction of lattice thermal conductivity are the phonon-liquid electron-crystal (PLEC) concept (which is based on the liquid-like behavior of superionic conductors) [2,12,13,16], bonding anisotropy in layered structures [8,17,18], lattice anharmonicity induced by the lone-pairelectrons [5,[19][20][21] and bonding inhomogeneity [22][23][24]. Following the market requirements, sulfides attract more attention recently and they are frequent objects of current investigations [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, many efforts were applied for the development of materials that consist of earth-abundant and environmentally friendly elements. Following this idea, a lot of attention was focused on the development of sulfides, especially the copper-based sulfide compounds such as Cu 2– x S, ternary Cu–Sn–S semiconductors, , chalcopyrites, cubanites, colusites, stannoidites, tetrahedrites, argyrodites, , and some other Cu-based sulfides. Despite good TE performance, some of these compounds (e.g., Cu 2– x S and argyrodites) are superionic conductors and their practical application is restricted due to low thermal stability accompanied by cation migration, which causes the structure degradation of the material. , …”
Section: Introductionmentioning
confidence: 99%